OGT and OGA gene-edited human induced pluripotent stem cells for dissecting the functional roles of O-GlcNAcylation in hematopoiesis - Luanpitpong, Sudjit; Tangkiettrakul, Kantpitchar; Kang, Xing; Srisook, Pimonwan; Poohadsuan, Jirarat; Samart, Parinya; Klaihmon, Phatchanat; Janan, Montira; Lorthongpanich, Chanchao; Laowtammathron, Chuti; Issaragrisil, Surapol (Frontiers in Cell and Developmental Biology, 2024)
Hematopoiesis continues throughout life to produce all types of blood cells from hematopoietic stem cells (HSCs). Metabolic state is a known regulator of HSC self-renewal and differentiation, but whether and how metabolic sensor O-GlcNAcylation, which can be modulated via an inhibition of its cycling enzymes O-GlcNAcase (OGA) and O-GlcNAc transferase (OGT), contributes to hematopoiesis remains largely unknown. Herein, isogenic, single-cell clones of OGA-depleted (OGAi) and OGT-depleted (OGTi) human induced pluripotent stem cells (hiPSCs) were successfully generated from the master hiPSC line MUSIi012-A, which were reprogrammed from CD34 + hematopoietic stem/progenitor cells (HSPCs) containing epigenetic memory. The established OGAi and OGTi hiPSCs exhibiting an increase or decrease in cellular O-GlcNAcylation concomitant with their loss of OGA and OGT, respectively, appeared normal in phenotype and karyotype, and retained pluripotency, although they may favor differentiation toward certain germ lineages. Upon hematopoietic differentiation through mesoderm induction and endothelial-to-hematopoietic transition, we found that OGA inhibition accelerates hiPSC commitment toward HSPCs and that disruption of O-GlcNAc homeostasis affects their commitment toward erythroid lineage. The differentiated HSPCs from all groups were capable of giving rise to all hematopoietic progenitors, thus confirming their functional characteristics. Altogether, the established single-cell clones of OGTi and OGAi hiPSCs represent a valuable platform for further dissecting the roles of O-GlcNAcylation in blood cell development at other stages and lineages of blood cells. The incomplete knockout of OGA and OGT in these hiPSCs makes them susceptible to additional manipulation, i.e., by small molecules, allowing the molecular dynamics studies of O-GlcNAcylation.